2014
DOI: 10.1186/2049-6958-9-57
|View full text |Cite
|
Sign up to set email alerts
|

Carrageenan nasal spray in virus confirmed common cold: individual patient data analysis of two randomized controlled trials

Abstract: BackgroundClinical trials applying iota-carrageenan nasal spray have previously shown to reduce duration of virus-confirmed common cold. The present study pooled data of two similar clinical trials to provide further evidence for the antiviral effectiveness of carrageenan.MethodsIndividual patient data were analyzed from two randomized double blind placebo controlled trials assessing the therapeutic effectiveness of carrageenan nasal spray in acute common cold. Patients with virus-confirmed common cold (n = 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
109
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 22 publications
1
109
0
3
Order By: Relevance
“…Consistent trends in favor of I-C for secondary endpoints and statistically significant outcomes for exploratory analyses were also observed for the ICICC trial. The finding that nominally greater treatment effects were seen in the ICICC trial among patients who were viruspositive, is supported by a pooled analysis by Koenighofer [14], which combined the Fazekas and Ludwig trials [6,7]. The pooled analysis examined only those patients who were virus-positive, and showed that nominal response rates were higher in virus-positive patients than in all participants of the Ludwig and Fazekas trials.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent trends in favor of I-C for secondary endpoints and statistically significant outcomes for exploratory analyses were also observed for the ICICC trial. The finding that nominally greater treatment effects were seen in the ICICC trial among patients who were viruspositive, is supported by a pooled analysis by Koenighofer [14], which combined the Fazekas and Ludwig trials [6,7]. The pooled analysis examined only those patients who were virus-positive, and showed that nominal response rates were higher in virus-positive patients than in all participants of the Ludwig and Fazekas trials.…”
Section: Discussionmentioning
confidence: 91%
“…Carrageenan has been extensively used in food, cosmetic and pharmaceutical industries, and is on the FDA's list of generally recognized as safe (GRAS) products for consumption (21 CFR 172.620). We demonstrated the antiviral effectiveness of iota-carrageenan against a variety of respiratory viruses in several preclinical and clinical trials; [21][22][23][24][25][26] therefore, it has been approved for marketing in the EU, Asia and Australia as part of a variety of over-the-counter products addressing common cold and related diseases.…”
Section: Discussionmentioning
confidence: 97%
“…[23][24][25] The pooled analysis of two studies conducted in 153 children and 203 adults revealed that patients infected with any respiratory virus who were intranasally treated with iota-carrageenan showed a 1.9-day faster recovery from common cold symptoms than placebo-treated patients in the intention-to-treat population. 26 Carrageenan is contained in medical device nasal sprays that have been approved and marketed in the EU for 10 years for the supportive treatment of common cold/flu-like illnesses caused by viruses.…”
Section: Introductionmentioning
confidence: 99%
“…We published that iota-carrageenan is a potent inhibitor of hRV [36] and influenza A [37] replication and demonstrated the antiviral efficacy of iota-carrageenan against common cold viruses by intranasal application in several randomized, double-blind, parallel group, placebo-controlled clinical trials [38][39][40]. The pooled analysis of two studies conducted in 153 children and 203 adults revealed that patients infected with any respiratory virus, who were intranasally treated with iota-carrageenan showed a 1.9 day faster recovery from common cold symptoms than placebo treated patients in the intention-to-treat population [41,42]. The anti-influenza activity was shown by subgroup analysis of 49 influenza infected patients who benefited from a 3.3 days faster recovery from symptoms.…”
Section: Introductionmentioning
confidence: 97%